Integrasi Prinsip Ekonomi Hijau dalam Perencanaan dan Penganggaran Sektor Publik: Systematic Literature Review (SLR) Berbasis PRISMA dalam Konteks Indonesia - Asrida Asrida; Miya Nurohmah (ProBisnis : Jurnal Manajemen, 2026)
The green economy represents a development paradigm that emphasizes the balance between economic growth, environmental sustainability, and social equity. In the context of developing countries such as Indonesia, the public sector plays a strategic role in integrating green economy principles through development planning and public budgeting instruments at both national and subnational levels. This study aims to systematically analyze the integration of green economy principles in public sector planning and budgeting using a Systematic Literature Review (SLR) method based on the PRISMA framework. The literature was collected from Scopus, Web of Science, and Google Scholar databases using rigorous inclusion and exclusion criteria. The findings indicate that Indonesia has normatively adopted green economy principles in key development planning documents, including the National Long-Term Development Plan (RPJPN), the National Medium-Term Development Plan (RPJMN), and Regional Medium-Term Development Plans (RPJMD), as well as through public budgeting instruments such as green budgeting and climate budget tagging. However, the implementation remains constrained by several challenges, including limited institutional capacity, weak policy coherence across levels of government, and underdeveloped environmental performance evaluation systems. This study contributes both conceptually and practically by strengthening the integrative framework linking planning, budgeting, and evaluation within the context of green economy policies, and by providing insights for enhancing sustainable public financial governance in Indonesia.